Історія туризму Галичини в антропологічному вимірі - Вербицька, Поліна; Verbytska, Polina (Lviv Politechnic Publishing House, 2019)
Статтю присвячено проблемі актуалізації потенціалу маловідомих сторінок історії туризму Галичини другої половини XIX ст. та його непересічних фундаторів. Виокремлено та узагальнено дослідницьке поле наукової проблематики історії й антропології туризму. Проаналізовано опис студентських мандрівок 1883–1885 рр., що міститься у нарисі Івана Крип’якевича «З історії галицького краєзнавства» як джерело історії й антропології туризму. З’ясовано потенціал історичних досліджень із туризмознавства як надбання європейського культурного туризму.

The article deals with the problem of actualizing the potential of largely unknown pages of the history of tourism in Galicia in the second half of the 19th century and emphasizing the role of its remarkable founders. The research field framing the scholarly issue of tourism history and anthropology is outlined and summarized. The main thesis of the article is that tourism anthropology enriches the history of tourism with a human dimension focusing on such aspects as studying motivation and behavior of tourists as well as exploring social, economic and cultural impact of tourism on the host population and society. Tourism activities in the past provide valuable information about social and cultural development and changes taking place in society. The given paper signifies the value of the sources of tourism history and anthropology in improving our understanding of interrelationships between leisure, culture and social changes. History of Galicia tourism was found out to be related to the activities of its founders Ivan Franko and Ivan Krypiakevych, who in their writings did not only stress the cognitive and educational value of tourist trips for Ukrainian society but also initiated tourism research activities of young scholars. Within the context of history and tourism anthropology Ivan Krypiakevich's essay «On the History of Galician Local History» (1932) is claimed to be of considerable interest. The work provides detailed description of six journeys of student youth in Galicia, Bukovyna and the Carpathians during the years of 1883–1888, which is based on the records of travelers and the chronicles of their touristic trip. The given research focuses on analysis of the description of student trips of 1883–1885 in the above mentioned essay as a source of history and anthropology of tourism. It has been underlined that the description of student trips in the work by I.Krypiakevych is a valuable source for the history and anthropology of tourism of the second half of the XIX century, giving clues for us to understand motivation and behavior of the journey participants as well as providing rich ethnographic materials and information about the Galician society common lifestyle and the public life of Ukrainians, which is the subject of study of anthropology and the property of the tourism history. Prospects of historical research into development of tourism science in Ukraine as an achievement of European cultural tourism history are revealed in the article.
History of tourism in Galicia within anthropological dimension
Keywords: історія туризму; антропологія туризму; туристичне краєзнавство; мандрівка; Галичина; history of tourism; anthropology of tourism; journey; local history; Galicia; 338.48(091); 572](477.83/.86)